1988
DOI: 10.1111/j.1476-5381.1988.tb11627.x
|View full text |Cite
|
Sign up to set email alerts
|

The relaxant and spasmogenic effects of some xanthine derivatives acting on guinea‐pig isolated trachealis muscle

Abstract: Switzerland1 Caffeine (10mM)-induced relaxation of guinea-pig isolated trachealis was attenuated and converted to a small spasmogenic response on cooling to 220C. The relaxant response was restored on rewarming to 370C and was abolished by indomethacin (2.8 pM). Cooling to 220C in the presence of indomethacin revealed spasmogenic responses to caffeine which were abolished on rewarming to 370C.2 Trachealis treated with indomethacin (2.8upM) was repeatedly dosed with acetylcholine (ACh, 10pM). Caffeine (1 or 10m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 10 publications
3
16
0
Order By: Relevance
“…Adenosine relaxed guinea pig trachea via an A 2B receptor (Brown and Collis, 1982;Karlsson and Persson, 1984). Relaxation of the trachea is also produced by xanthines, but this is independent of adenosine antagonism (Darmani and Broadley, 1986;Small et al, 1988). Advenier et al (1988) suggested that epithelium had an influence on the mechanical response of guinea pig trachea to adenosine, but a later article (Thorne and Broadley, 2001) did not support this possibility.…”
Section: B Smooth Muscle and Its Innervationmentioning
confidence: 91%
“…Adenosine relaxed guinea pig trachea via an A 2B receptor (Brown and Collis, 1982;Karlsson and Persson, 1984). Relaxation of the trachea is also produced by xanthines, but this is independent of adenosine antagonism (Darmani and Broadley, 1986;Small et al, 1988). Advenier et al (1988) suggested that epithelium had an influence on the mechanical response of guinea pig trachea to adenosine, but a later article (Thorne and Broadley, 2001) did not support this possibility.…”
Section: B Smooth Muscle and Its Innervationmentioning
confidence: 91%
“…In vascular smooth muscle, caffeine also releases cellular calcium to induce a transient contraction (Leijten & Van Breemen, 1984;Karaki et al, 1987). In addition to these contractile effects, caffeine has an inhibitory action in various smooth muscles, including myometrium (Ito & Kuriyama, 1971;Ashoori et al, 1985;Ahn et al, 1988;Small et al, 1988). Caffeine also inhibits cyclic adenosine 3',5'-monophosphate (cyclic AMP) phosphodiesterase leading to accumulation of intracellular cyclic AMP (Ahn et al, 1988;Bray et al, 1989) and decrease of cytoplasmic calcium concentration (Sato et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The methylxanthine, caffeine, is also well established as releasing intracellular Ca2 + from smooth muscle cells (Leijten & van Breemen, 1984;Benham & Bolton, 1986). In airway smooth muscle, caffeine can evoke contraction by liberation of intracellular Ca2+ (Ito & Itoh, 1984;Small et al, 1988).…”
Section: Introductionmentioning
confidence: 99%